Study of Cobalt Adsorption from Aqueous Solution on Granular Activated Carbon - Khope, R.U.; Halmare, S.S.; Natarajan, G.S. (Asian Journal of Chemistry, 2016)
Studies on removal of cobalt from aqueous solution by adsorption on granular activated carbon (GAC) containing adsorbed 3,5-dinitrosalicylic acid (DNSA) have been carried out at temperature 25 ± 0.5°C. The adsorption isotherm of Co on GAC have been determined and the data fitted reasonably well to the Langmuir and Freundlich isotherm for activated carbon.